Problems and Promises of Qualitative Secondary Analysis for Research in Information Science - Vanscoy, Amy; Bossaller, Jenny; Burns, C. Sean (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2018)
Qualitative secondary analysis (QSA) is a method that has been used in other disciplines and debated from epistemological and ethical perspectives. It has rarely been explicitly used or discussed in information science. This paper explains value of the method for information science research, discussing its benefits and challenges and analyzing our recent QSA study.